Development and optimization of organic-based chemosensor for cation and anion recognition in aqueous medium - Nurul Amirah Baharu (Kulliyyah of Science, International Islamic University Malaysia, 2021)
Heavy metal toxicity has proven to be a major threat and exhibit a several health risks associated with it. The use of thiosemicarbazone has recently gained interest as potential receptors regarding to the ease of synthetic approach and possess to active chelating sites. Chemosensor is an alternative devices and developed by organic-based that have the ability to recognize metal ion or anion in aqueous medium by displaying colour change upon detection of targeted ion. Therefore, in this research study, we have developed four organic-based chemosensor namely 2-acetylpyrrole thiosemicarbazone (AP1) and 3-acetylpyridine 2-hydroxylphenyl thiosemicarbazone (AP4) for Cu2+ recognition meanwhile 3-acetylpyridine thiosemicarbazone (AP2) and 4-aminoacetophenone thiosemicarbazone (AP3) for IO3- recognition, respectively. All the chemosensors were favourable to DMSO solvent where they showed the strong interaction binding in solvent-ligand interaction. The results showed that AP1 produced high absorbance in 5:5 ratio with co-solvent, AP4 in 8:2 ratio while AP2 and AP3 shared the same ratio which is 9:1 ratio. Both ligands AP1 and AP4 were good making interaction in pH 7 neutral while AP2 and AP3 were optimum in pH 11 alkali. Interference analysis indicate that chemosensor AP1 - AP4 did not involve in any interference from other tested metal ions and anions. The interaction of all the ligand complex had clearly observed on its respected wavelength and the colour for all ligand complex were also successfully changed upon the recognition of metal ion and anion. The experimental data had identified the AP1 chemosensor coordinates Cu2+ ion in 1:1 stoichiometry, while AP4 is in 2:1 stoichiometry. In other hand, AP2 and AP3 coordinates IO3- showed the 2:1 stoichiometry for both chemosensor. Using computational study of COSMO-RS, it showed the compatibility of AP1 - AP4 with the solvent DMSO through hydrogen bonding interaction. The DFT study and calculations were conducted to analyse the stability of the formation of energy complex and their stability. The application of the chemosensor AP1-AP4 towards environmental samples, which were distilled water, tap water and lake water were successfully showed the positive results in recognition of Cu2+ and IO3- ion. In this study, the detection limit of chemosensor AP1 was determined at 41.8 µM and at 67.9 µM for AP4. Moreover, the detection limit of AP2 and AP3 chemosensor were determined at 114 µM and 788 µM, respectively. Thus, all respective thiosemicarbazone-based chemosensor were successfully able to make a recognition for aqueous Cu2+ and IO3- ions as they can served as affordable, portable, convenient and can used as off-site device.